Optimal treatment project for schizophrenia: results from a randomized, controlled, longitudinal study - (:unkn) unknown (My University, 2003)
This study aimed to compare the clinical and social benefits associated with Optimal Case Management (OCM) treatment that employ cognitive-behavioural strategies to those associated with Routine Case Management (RCM) that is widely used in community health services. Hundred patients with schizophrenia were randomly allocated to OCM and RCM treatment conditions. Patients in the OCM condition showed significantly more improvement on all measures compared to patients in RCM condition. Improvement on clinical symptoms and social functioning achieved by OCM tended to show a regular and continuous pattern throughout the course of the study. The results of this study suggest that every optimal treatment should aim improvement in social functioning and therefore quality of life of the patients.
Keywords: Adult; Female; Humans; Middle Aged; Adolescent; Male; Longitudinal Studies; Antipsychotic Agents; Benzodiazepines; Olanzapine; Pirenzepine; Patient Care Team; Adaptation, Psychological; Case Management; Cognitive Behavioral Therapy; Schizophrenia; Community Mental Health Services; Haloperidol; Quality Assurance, Health Care